2017
DOI: 10.1186/s12889-017-4418-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-child co-participation in physical activity-related behaviours: prevalence and cross-sectional associations with mothers and children’s objectively assessed physical activity levels

Abstract: BackgroundCo-participation in physical activity may be a useful strategy for increasing physical activity in mothers and their young children, yet little empirical evidence exists on this topic for young families. This study aimed to identify the prevalence of mother-child co-participation in physical activity and examine the association between co-participatory behaviours and objectively-assessed physical activity in young children and their mothers.MethodsOne-hundred twenty-three 4–6 year-old children and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…However, to our knowledge, only one study has specifically studied the influence of co-participation in PA on pre-school children’s activity levels. Hnatiuk [ 27 ] discovered most Belgian mothers reported infrequent co-participation in PA with their children. In particular, walking or cycling together was associated with higher PA at weekends in both children and mothers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, only one study has specifically studied the influence of co-participation in PA on pre-school children’s activity levels. Hnatiuk [ 27 ] discovered most Belgian mothers reported infrequent co-participation in PA with their children. In particular, walking or cycling together was associated with higher PA at weekends in both children and mothers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hnatiuk [ 27 ] discovered most Belgian mothers reported infrequent co-participation in PA with their children. In particular, walking or cycling together was associated with higher PA at weekends in both children and mothers [ 27 ]. Other studies have concluded that higher parental PA levels are associated with higher PA levels of pre-school children [ 28 ], but have not specified whether the activity was performed together.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that parents play a critical role in developing and shaping the PA and sedentary behavior of their children through role modelling [ 6 , 7 , 8 ]. Previous studies on primary school aged children and their parents have examined the associations between objectively measured PA or sedentary time in parents and their children [ 6 , 7 , 9 ]. However, a recent systematic review pointed out that only a few studies have examined the effect of fathers on children’s PA and this relationship remains unclear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, sedentary board games or screen-based leisure options could be replaced with active games and sports to increase the physical activity of the mother and the child. Further, a study of the mothers' participation in MVPA with their preschoolers in Belgium [29] found that recreational walking and cycling with their children on weekends was significantly associated with MVPA among mothers and their children.…”
Section: Discussionmentioning
confidence: 99%